LOWER KARROO (PERMlAN) ACANTHOMORPHITAE ACRlTARCHS FROM SOUTH AFRICA - Hart, George F. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1969)
Eight populations of fifty individuals of Acritarchs from the Permian marine horizons of South Africa are statistically analysed and assigned to two species of Micrhystridium. The use of the multivariate discriminant function and Mahalanobis- D2 as a taxonomic tool in distinguishing populations and species that have but few measurable variables is briefly discussed and the possibility of using such techniques to determine stratigraphic position in lineage studies noted.